The Crowfield demon - Walsh, Pat, 1954- (New York : Scholastic, 2012)
In March of 1348, the awakening of an ancient evil drives fay creatures from the woods, causes Crowfield Abbey to crumble, and haunts the dreams of the monks, but the demon seems especially drawn to Will, who is beginning to realize the significance of his Sight.
Sequel to: The Crowfield curse.
Keywords: Orphans -- Fiction; Demonology -- Fiction; Magic -- Fiction; Identity -- Fiction; Monasteries -- Fiction; Blessing and cursing -- Fiction; Great Britain -- History -- 14th century -- Fiction; Orphans -- Juvenile fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Identity -- Juvenile fiction; Monasteries -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Great Britain -- History -- 14th century -- Juvenile fiction